A novel methodology for characterizing fracture process zone evolution in Barre granite specimens under mode I loading. (February 2023) - Garg, Prasoon; Zafar, Sana; Hedayat, Ahmadreza; Moradian, Omid Z; Griffiths, D.V.
Highlights: A novel DIC-based methodology was developed for characterizing the evolution of the fracture process zone in Barre granite specimens. The size of the process zone obtained from the DIC-based methodology was corroborated with AE-based measurements. The linear cohesive zone model based on the DIC analysis was found to be suitable for defining the inelastic deformation inside the process zone. Abstract: Fracturing in quasi-brittle such as rock involves the development of an inelastic zone around the pre-crack tip, also known as the fracture process zone (FPZ). The evolution of FPZ, while influencing the fracture behavior of rocks, is difficult to characterize due to the localized nature of material behavior and microstructural heterogeneities. This study presents a digital image correlation technique (DIC)-based method that consistently describes the FPZ evolution in mode I fracture of Barre granite specimens. The FPZ characteristics were also evaluated using acoustic emission (AE) monitoring. The evolution of the crack tip opening displacement ( C T O D ) was analyzed to estimate the various fracture parameters, such as threshold values of the elastic and critical opening displacements and the size of the fully developed FPZ. The comparison of DIC-based measurements with the AE-based microcracking activities demonstrated that the displacement approach of the former could be used independently to identify the transition among the three stages of FPZ evolution, namely, (1) elastic stage, (2) formation of FPZ, and (3) macro-crack initiation. Experimental results also indicate a linear relationship between the FPZ length and the inelastic component of the CTOD, along with the quadratic relationship between the local dissipated energy and the FPZ length, which is consistent with the linear softening law for material inside the FPZ.